Menghidupkan Kembali Warisan Keilmuan Islam melalui Pembelajaran Aksara Pegon dan Kitab Sunan Drajat dalam Meningkatkan Literasi Santri - Moh. Badrus Solichin; Mochamad Dimas Syarifullah; Rendra Patmoko; Muhammad Ainul Yaqin; Shinta Trisyah Rahmah; Siti Izatul Muthiah; Nopra Efendi; Nintya Ananda Putri; Nela Novita Sari; Fidia Rachmawati; M. Akmal Arifani Nur Badry (NAJWA: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2025)
This community service program aims to develop the application of the Pegon script learning method to improve students' Islamic literacy through the study of the Sunan Drajat book at TPQ Mamba'ul Ulum. This community service program uses an Asset-Based Community Development (ABCD) approach, focusing on exploring local assets, such as teachers with Islamic boarding school backgrounds and students' basic ability to read Arabic letters. The teaching method used is interactive, including questions and answers, discussions, and writing practice on the blackboard. The results of the activity show a significant increase in students' ability to read Pegon texts and their understanding of contextual Islamic values. The application of this method successfully demonstrates that the Pegon script is not just a reading and writing tool but an effective medium for connecting students with the traditions of Nusantara Islam and local culture. This program can empower TPQ's internal assets and foster students' pride in the heritage of Islamic knowledge. It is concluded that the Pegon learning method, based on local books, is highly relevant to strengthening students' Islamic literacy and identity in the contemporary era.